PENGARUH KONSENTRASI JELLY POWDER TERHADAP KARAKTERISTIK MINUMAN JELI IKAN LELE (Clarias sp.) - Willy Pranata Widjaja; sumartini . (Pasundan Food Technology Journal (PFTJ), 2018)
The motive of research is to find out how to make a jelly drink from catfish. While the purpose of this researchis to determine the effect of jelly powder concentration on the characteristics of catfish jelly drink. The benefits of this research is to provide a reference processing functional beverage made from animal foods, provide product information diversification catfish jelly drinks,manufacturing process of catfish jelly drink and accurate concentrate jelly powder also panelists preferred to make a catfish jelly drink.The research was conducted in two stages; preliminary research and primary research. Preliminary research was involve the removal of the fishy smell, raw materials analysis and determining the ratio of meat catfish and the water that used in the primary research. The method was used in this research is a randomized block design (RBD) with 12 × 1 factorial with two replications. Variable concentrations of jelly powder were used to make a catfish jelly drink is f1 (0.10%), f2 on (0.15%), f3 (0.20%), f4 (0.25%), f5 (0.30%), f6 (0.35%), f7 (0.40%), f8 (0.45%), f9 (0.50%), f10 (12:55%), f11 (0.60%) and f12 (0.65%). Based on the results of research, concentration of jelly powder give significant effect on water content, viscosity, total dissolved solids, color, flavor, texture and appearance of jelly drinks catfish but it is not give significant effect on reducing sugar content and smell. Selected samples of the research are f7 with the concentration of jelly powder as much as 0.40% and that catfish jelly drinks contains moisture 80.15%, levels of reducing sugars 1.175%, viscosity 1:53 dPas, total dissolved solids 18.7 ° Brix, protein content 3.72% and levels 1.78% crude fiber.